Maternal and Fetal Factors Affecting Neonatal Outcome of Emergency Caesarian Section at Northern Mindanao Medical Center: A Secondary Analysis - Cruz, Carolyn R. (JPAIR Multidisciplinary Research, 2008)
The study identifies maternal and fetal factors in outcomes of babies born to mothers who underwent emergency caesarian operation at NMMC recorded during the period covering 2002-2003. From the recorded births, the study yielded 368 mothers and 392 babies. Findings include average of mother who underwent emergency caesarian section (ECS) to be between 18-35 years with 2-5 pregnancies and/or deliveries. Outcomes of these ECS indicated a significant proportion of 36.7 percent of the babies born with an APGAR score of below 7 signifying varying degrees of depression and death of few babies (6.0 percent). Maternal factors were found the most frequent indication for ECS (50.0 percent of cases). Mothers more than 35 years old or with more than 5 preganancies and/or deliveries and those who were having babies below 37 weeks or above 41 weeks were found to be associated with poor outcomes or baby conditions. Hypertension followed by prenatal maternal bleeding and multiple medical problems were also noted for producing poor neonatal outcomes. Among the fetal factors found to produce poor neonatal outcomes are: abnormal FHR, oligohydraminios, cord prolapse, multiple fetal problems, meconium stain in IE, etc. Of these, cord prolapse was observed to the most dreaded fetal factor (50.0 percent of the babies).
Keywords: Maternal and Fetal Factors; Neonatal Outcome; Emergency Caesarian